2006
DOI: 10.1091/mbc.e05-11-1001
|View full text |Cite
|
Sign up to set email alerts
|

PAK1 and aPKCζ Regulate Myosin II-B Phosphorylation: A Novel Signaling Pathway Regulating Filament Assembly

Abstract: Many signaling pathways regulate the function of the cellular cytoskeleton. Yet we know very little about the proteins involved in the cross-talk between the signaling and the cytoskeletal systems. Here we show that myosin II-B, an important cytoskeletal protein, resides in a complex with p21-activated kinase 1 (PAK1) and atypical protein kinase C (PKC) zeta (aPKC) and that the interaction between these proteins is EGF-dependent. We further show that PAK1 is involved in aPKC phosphorylation and that aPKC phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 50 publications
3
79
1
Order By: Relevance
“…44,47 Moreover, different signaling pathways control the assembly of each myosin II isoform as the kinetics of myosins IIA and IIB phosphorylation upon agonist stimulation of mammalian cells differ and separate members of the PKC family, specifically, phosphorylated myosins IIA and IIB. 26,27,45 We conclude that both myosins IIA and IIB are regulated by heavy chain phosphorylation in vivo but that specific signaling pathways control the assembly of these different myosin II isoforms.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…44,47 Moreover, different signaling pathways control the assembly of each myosin II isoform as the kinetics of myosins IIA and IIB phosphorylation upon agonist stimulation of mammalian cells differ and separate members of the PKC family, specifically, phosphorylated myosins IIA and IIB. 26,27,45 We conclude that both myosins IIA and IIB are regulated by heavy chain phosphorylation in vivo but that specific signaling pathways control the assembly of these different myosin II isoforms.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, detecting the phosphorylation of a particular site on myosin II generally requires the mutation of several residues that are phosphorylated by other kinases. 27 Moreover, the TRPM7 kinase is low in abundance relative to other kinases. Based on the low expression levels, we do not believe that TRPM7 is responsible for the global regulation of myosin IIA dynamics in mammalian cells and that additional mechanisms are in place for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is possible that NMHC II-B serves as a downstream target of aPKC in regulating cell adhesion in the spinal canal, there are other putative targets in the neuronal adherens junction as well, such as PAR3 and Lgl1 (Yamanaka et al, 2003;Klezovitch et al, 2004;Suzuki and Ohno, 2006;Vasioukhin, 2006). In contrast, Even-Faitelson and Ravid (2006) have reported that phosphorylation of the NMHC II-B in the nonhelical tail by an aPKC results in cortical localization of both NM II-B and aPKC in a prostate cancer cell line. The requirement of aPKC in cell-cell adhesion has been demonstrated both in cultured cells (Suzuki et al, 2001, Nunbhakdi-Craig et al, 2002 and neuroepithelial cells in the developing mouse brain (Manabe et al, 2002).…”
Section: Cell-cell Adhesion Of the Neuroepithelial Cells Requires Nonmentioning
confidence: 98%
“…While HC phosphorylations at multiple sites modulate M2B filament formation (Murakami et al 2000;Even-Faitelson and Ravid 2006), metastasis-associated protein, S100A4 (a.k.a. Mts1), binds to the C-terminal end of the α-helical tail of M2A in a calcium-dependent manner and blocks the critical filament assembly site including the site for PKCβII phosphorylation at Ser1917, directly inhibiting filament assembly and leading to an inhibition of MgATPase activity (Ford et al 1997;Kriajevska et al 1998;Li and Bresnick 2006).…”
Section: The Players: Binding Partners and Regulationmentioning
confidence: 99%